Selling price, time dependent demand and variable holding cost inventory model with two storage facilities. (2022) - Aarya, Deo Datta; Rajoria, Yogendra Kumar; Gupta, Neha; Raghav, Yashpal Singh; Rathee, Rakesh; Boadh, Rahul; Kumar, Ajay
Abstract: Customer service stock-out rates, as well as the company's business sales and marketing productivity, are controlled by the storage facility (warehouse). In this study, a two- storage production inventory model with demand dependent on price and time described. The rate of demand is governed by the selling price and the time. In this analysis, we hypothesized that the deterioration rate is constant and that the holding cost for own storage is time-dependent (OW). For rental storage, the deterioration rate is considered to be time-dependent, while the holding cost is assumed to be constant (RW) which is more realistic. This study assists to reduce total inventory costs by finding the best replenishment strategy. A numerical example is used to demonstrate the model's method, as well as a sensitivity analysis on a few parameters.